2020
DOI: 10.5539/ibr.v13n6p115
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Challenges of Complex Products: Case of Goldman Sachs and the Synthetic Collateralized Debt Obligations

Abstract: In analyzing complex products, this study selected the company Goldman Sachs and one of its product offerings, the synthetic collateralized debt obligation (synthetic CDO). The study later analyzed the ethical implications of providing such a complex product to customers. A review of the literature indicates that researchers identified this product and other associated derivatives of the mortgage backed securities as the main causes of the 2008 financial crisis in the United States of America. As such, Goldman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The simulation of 100 months of a strategic decision to source from Singapore revealed that any instability in the supply chain would increase costs and expenses, disrupt production, and decrease revenue and satisfaction. That is exactly what happened around the world with the 2008 economic and financial crisis (Lartey, 2020) or the 2019 corona virus spread (COVID-19) that became a pandemic in 2020 (Remuzzi & Remuzzi, 2020). Levy's study suggests that managers can use chaos theory as a framework to account for dynamic evolution and complex interactions that disrupt organizations.…”
Section: Implications For Organizational Leadersmentioning
confidence: 86%
“…The simulation of 100 months of a strategic decision to source from Singapore revealed that any instability in the supply chain would increase costs and expenses, disrupt production, and decrease revenue and satisfaction. That is exactly what happened around the world with the 2008 economic and financial crisis (Lartey, 2020) or the 2019 corona virus spread (COVID-19) that became a pandemic in 2020 (Remuzzi & Remuzzi, 2020). Levy's study suggests that managers can use chaos theory as a framework to account for dynamic evolution and complex interactions that disrupt organizations.…”
Section: Implications For Organizational Leadersmentioning
confidence: 86%
“…This failure was later altered by cautious management of the new CEO in 1950s. The managers of Goldman Sachs have commented that in order to ensure "long lasting greed", it is essential for the corporation to value reputation by approaching investment opportunities with cautious actions [9]. However, during the financial crisis, Goldman Sachs' attitude towards risk in financial instruments has given rise to moral and ethical considerations of how it might be suggestive to questioning outcomes.…”
Section: Influence Of Investment Banks On Debt Management and Equity ...mentioning
confidence: 99%
“…However, during the financial crisis, Goldman Sachs' attitude towards risk in financial instruments has given rise to moral and ethical considerations of how it might be suggestive to questioning outcomes. In the case proposed by Lartey (2020), it argued that Goldman Sachs has caused conflicts of interests between the investment bank and its clients through participating in insurance activities [9]. The case proposed in the article is Abacus 2007-AC1, where the deal enables policy holders to obtain insurance returns upon investment failure of their bet.…”
Section: Influence Of Investment Banks On Debt Management and Equity ...mentioning
confidence: 99%